The Immunomodulatory Effects of Plant Extracts and Plant Secondary Metabolites on Chronic Neuroinflammation and Cognitive Aging: A Mechanistic and Empirical Review - Kure, Christina; Timmer, Jorinde; Stough, Con (Frontiers in Pharmacology, 2017)
Advances in healthcare have considerably improved the life expectancy of the human population over the last century and this has brought about new challenges. As we live longer the capacity for cognitive aging increases. Consequently, it has been noted that decline in cognitive performance in the elderly in domains of reasoning, problem solving skills, attention, processing speed, working memory and episodic memory is a significant societal problem. Despite the enormity of this issue there are relatively few interventions for cognitive aging. This may be due to our current state of knowledge on biological factors that underpin cognitive aging. One of the biological contributors to cognitive aging is chronic neuroinflammation. This review will provide an overview of the peripheral and central mechanisms involved in chronic neuroinflammation and how neuroinflammation may be related to age-associated cognitive decline. Plant based extracts including herbal and nutritional supplements with anti-inflammatory properties will be examined in relation to their utility in treating age-related cognitive decline. Plant based extracts in particular offer interesting pharmacological properties that may be quickly utilized to prevent cognitive aging.